COMPREHENSIVE GUIDANCE AND COUNSELING FOR GIFTED CHILDREN THROUGH THE APPLICATION OF MILGRAM’S MODEL IN ACCELERATION-INCLUSION SETTING - Suherman, Yuyus; Kartadinata, Sunaryo; Yusuf, Syamsu; Alimin, Zaenal (International Journal of Education, 2015)
Acceleration program is claimed to be designated for gifted children. However, the implementation of the program is still considered sporadic and exclusive. This study aims at developping a comprehensive guidance and councelling for gifted child using Molgram’s model in acceleration inclusion setting. The research question is “ how is the development of comprehensive guidance and counseling for gifted children through Milgram’s model in acceleration-inclusion setting applicable and affective?". This research applied mixed methods as its design which utilize researchand development as the umbrella in three phases. The first phase, a preliminary study which produced a hypothetic model. The finding shows that comprehensive guidance and councelling for gifted children in acceleration-inclusion setting (the model) can be constructed based on home, school, and community; it can be implemented to non-gifted, mildly gifted, moderately gifted, and profoundly gifted children, focusing on general critical thinking, specific creative talent, general intelligence, and specific intellectual ability. The comprehensive guidance and councelling should also implement assessment, planning, implementation, and evaluation as well as integration with context. The second stage was the conceptual and empirical validation, which generated an operating model to be tested for its effectiveness in the third stage.